Motivation and Life Circumstances Affecting Living Habits Prior to Gastrointestinal Cancer Surgery- An Interpretative Phenomenological Analysis - Karin Blomquist RN/NP, MScN; Carina Wennerholm RN, PhD; Carina Berterö RN; Per Sandström MD; Bergthor Björnsson MD; Jenny Drott RN, PhD (SAGE Publishing, 2023)
The aim was to explore the patient's experiences to get insights into their living habits prior to gastrointestinal cancer surgery. An interpretative phenomenological analysis (IPA) approach was used. Six in-depth interviews with participants recruited from a hospital in southeast Sweden. The IPA analysis identified 3 themes: The influence of the cancer diagnosis on awareness and motivation, Life circumstances affecting living habits , and Activities bringing mental strength . The participants expressed their motivation level and circumstances in life. Various types of activities and support promoted physical and mental health. Motivation level and circumstances in life both influence living habits. Various kinds of activities and support promote patients' physical and mental health. Nurses need to investigate patients' experiences when developing person-centered support to achieve health-promoting behavior prior to cancer surgery.